Acidity-driven gas-particle partitioning of nitrate regulates its transport to Arctic through the industrial era - Yoshinori Iizuka; Mai Matsumoto; Kaoru Kawakami; Mahiro Sasage; Sakiko Ishino; Shohei Hattori; Ryu Uemura; Hitoshi Matsui; Koji Fujita; Naga Oshima; Andrea Spolaor; Anders Svensson; et al. (Nature Communications)
Abstract Anthropogenic NOx emissions have altered the biogeochemical nitrogen cycle since the Industrial Revolution, yet Arctic ice core nitrate (NO3 −) records are inconsistent with post-1970s NOx emission reductions. Here we show a NO3 − deposition history covering 1800–2020 using an ice core from the southeastern Greenland dome with high snow accumulation. The ice core NO3 − concentrations are particularly disconnected from NOx source regions during the peak pollution period and post-1990s. A global chemical transport model reproduced these discordances between total NO3 − and NOx emissions by altering gaseous HNO3 and particulate NO3 − (p-NO3 −) ratios and subsequently NO3 − lifetime. This result and correlations with acidity parameters recorded in the ice core, suggest that acidity-driven gas-particle partitioning of NO3 − regulates its transport to Arctic regions alongside changes in NOx emissions. In the future, despite NOx reductions, the increase in proportion of p-NO3 − with longer atmospheric lifetime becomes crucial to control the Arctic NO3 − burden.